DOI: 10.11606/t.10.2016.tde-27092016-153001
|View full text |Cite
|
Sign up to set email alerts
|

<b>Criopreservação de sêmen de primatas não-humanos</b>

Abstract: Aos meus irmãos, Mateus e Paulo, pelos conselhos e por sempre "estarem lá" À minha grande família, incluindo tios, tias, primos e primas, pelo apoio incondicional e reuniões descontraídas.Aos meus amigos e amigas que, de longe ou de perto, sempre fizeram a diferença.Ao meu coorientador e amigo, Prof. Rodrigo R. Valle, por ter me incentivado e me ajudado a entrar na pós-graduação; por ter me introduzido à área de À técnica e amiga Cathy Ramsey, do ART Core, que me ajudou durante toda a realização do meu projeto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
3
0
2
Order By: Relevance
“…Analysis of thawed samples revealed encouraging results for Neotropical primates regardless of the treatment as, for example, high total and progressive motilities and increased plasma membrane integrity (above 50%, 40%, and 80% respectively). On average, sperm cryopreserved with BB tended to show better total motility ( p = .0571), but both extenders presented greater postthaw motility than most of the values reported for Neotropical primates (Arakaki, Nichi et al, ; Carvalho, ; Leão et al, ; O'Brien et al, ; Oliveira et al, ; Silva et al, ; Valle, ; Yeoman et al, ). Additionally, we observed that there were no significant differences between extenders for most seminal parameters, excepting TBARS and intact acrosome.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Analysis of thawed samples revealed encouraging results for Neotropical primates regardless of the treatment as, for example, high total and progressive motilities and increased plasma membrane integrity (above 50%, 40%, and 80% respectively). On average, sperm cryopreserved with BB tended to show better total motility ( p = .0571), but both extenders presented greater postthaw motility than most of the values reported for Neotropical primates (Arakaki, Nichi et al, ; Carvalho, ; Leão et al, ; O'Brien et al, ; Oliveira et al, ; Silva et al, ; Valle, ; Yeoman et al, ). Additionally, we observed that there were no significant differences between extenders for most seminal parameters, excepting TBARS and intact acrosome.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, 5 of the 25 most endangered primate species in the world live in the Neotropics (Schwitzer et al, ), and yet no standard sperm cryopreservation protocols have been described for these species. In the literature a few studies have investigated sperm freezing in species like squirrel monkeys, spider monkeys, howler monkey, capuchin monkey, marmosets, and tamarins (Arakaki, Nichi et al, ; Carvalho, ; Denis, Poindexter, Ritter, Seager, & Deter, ; Leão et al, ; Morrell et al, ; O'Brien, Hollinshead, Evans, Evans, & Maxwell, ; Oliveira et al, ; Oliveira, Leão, Almeida, Santos, & Domingues, ; Sankai, Tsuchiya, Ogonuki, Cho, & Yoshikawa, ; Silva et al, ; Yeoman, Ricker, Hossain, & Abee, ). However, the variety of protocols and their respective outcomes (Table ) makes it difficult to reach a consensus regarding an ideal method designed to routinely cryopreserve sperm from these primates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os planos PDCA usaram o método: 1) Planejar ("Plan"), 2) Desenvolver ("Do"): 3) Conferir ("Check") e 4) Atuar ("Action") (Basu, 2004;Soković et al, 2009 Em relação a análise econômica, foi observado que o APOIA-NovoRural propiciou apenas uma avalição superficial, apontando de forma qualitativa os pontos a serem melhorados (Figura 4A e 4B). Esse indicador é de extrema importância na propriedade, pois baseado no mesmo os gestores podem realizar tomada de decisões assertivas (Marion;Santos, 1993), imprescindíveis para uma pecuária de corte sustentável, econômica, social e financeiramente (Carvalho;De Zen, 2017). (Silva, 2010), impacta positivamente na capacidade produtiva do solo seguido do indicador de biodiversidade (Silva, 2012) 2 .…”
Section: Methodsunclassified
“…Finalmente, a pecuária no Brasil foi classificada como altamente sustentável com capacidade de adaptação a situações adversas. As possibilidades de concorrência com outras atividades agrícolas sinalizavam para probabilidade de desestruturação da cadeia da carne no país (CARVALHO;TAVARES, 2007). Moreira et al (2009) estudaram a análise econômica e os custos de produção do confinamento em Goiás, período de 2008, que combinasse garantia de rentabilidade com operações no mercado futuro.…”
Section: Custo Da Produção Pecuária Bovina De Corteunclassified